2018
DOI: 10.14336/ad.2018.0203
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Fatigue Does Not Change the Effects on Lower Limbs Strength Caused by Aging and Parkinson’s Disease

Abstract: The aim of this study was to determine the impact of aging and Parkinson’s disease (PD) on lower limb muscle strength before and after muscle fatigue. One hundred thirty-five individuals were distributed over seven groups according to their age (20, 30, 40, 50, 60, 70 years old) and disease. Participants performed maximum voluntary isometric contractions (MVIC) in a leg press device followed by the muscle fatigue protocol (repeated sit-to-stand task). Immediately after muscle fatigue (less than 2 min), the MVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Forty studies6,7,22–59 assessed MMF in PwPD versus HC (study characteristics are available in Supplemental Digital Content 2 Table 1d, available at: http://links.lww.com/JNPT/A404). Muscle strength was assessed in 37 studies6,7,22–37,39–43,45–47,49–59 (see Table, Supplemental Digital Content 3, available at: http://links.lww.com/JNPT/A406) while 12 studies reported RFD25,26,29 (p) ,31,38,43,44,46,50,54,57,58 and 1 study48 reported power outcomes (Table 1). Study sample sizes ranged from 6 to 61 PwPD and from 6 to 37 HC, summing to a total of 718 PwPD and 633 HC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty studies6,7,22–59 assessed MMF in PwPD versus HC (study characteristics are available in Supplemental Digital Content 2 Table 1d, available at: http://links.lww.com/JNPT/A404). Muscle strength was assessed in 37 studies6,7,22–37,39–43,45–47,49–59 (see Table, Supplemental Digital Content 3, available at: http://links.lww.com/JNPT/A406) while 12 studies reported RFD25,26,29 (p) ,31,38,43,44,46,50,54,57,58 and 1 study48 reported power outcomes (Table 1). Study sample sizes ranged from 6 to 61 PwPD and from 6 to 37 HC, summing to a total of 718 PwPD and 633 HC.…”
Section: Resultsmentioning
confidence: 99%
“…com/JNPT/A404). Muscle strength was assessed in 37 studies 6,7,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][39][40][41][42][43][45][46][47][49][50][51][52][53][54][55][56][57][58][59] (see Table, Supplemental Digital Content 3, available at: http://links.lww.com/JNPT/A406) while 12 studies reported RFD 25,26,29(p),31,38,43,44,46,50,54,57,58 and 1 study 48 reported power outcomes (Table 1). Study sample sizes ranged from 6 to 61 PwPD and from 6 to 37 HC, summing to a total of 718 PwPD and 633 HC.…”
Section: Aim 2: Comparison Of Mechanical Muscle Function In Pwpd Vers...mentioning
confidence: 99%
“…They can appear early in the course of PD, with increasing severity along with the progression of the disease. Furthermore, because of the disabling characteristics of these dysarthrias, approximately 70% of patents with PD suffer from worsening quality of life [11,32–37], such as reduced communication function [38,39], declined social contact [8,12] or increasing feelings of social isolation [40]. Thus, patients tend to start to paying attention to dysarthria in the mid to late stage rather than early in the disease course.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Huang et al (12) reported more exercise-induced fatigue in PD than in the healthy controls after a protocol of isometric knee extension. Instead, in a recent investigation Alota Ignacio Pereira et al (25) revealed similar values of force isometric voluntary contractions, after a repeated sit-to-stand task to induce fatigue, in patients with mild to moderate PD and healthy controls. The results of our study, differently from the initial hypothesis, agree with this interesting finding of Alota Ignacio Pereira et al and reinforce the idea that NF may be independent of PD symptoms.…”
Section: Discussionmentioning
confidence: 92%